Spectral Density Method of Liquid Propellant Gauging - Ananda, Celestine Elyse (Proceedings of the Wisconsin Space Conference, 2020)
My summer internship experience with NASA Kennedy Space Center’s Advanced Engineering Development Branch focused on collecting and processing data to aid in developing Modal Propellant Gauging (MPG) for use in future Orion/SLS missions. The MPG project is an effort to develop a non-invasive low-cost propellant mass gauging technology for application to existing spacecraft propellant tanks in both low-gravity and earth-loading applications. During my internship I constructed a fuel gauging framework through characterizing the modal signature of a composite-overwrap liquid propellant tank used for testing purposes. I accomplished this through: writing and implementing algorithms that apply broadband white noise signals to piezoelectric actuators adhered to the tank surface, processing acoustic data using Fourier analysis, and producing frequency response functions to experimentally determine resonant modes of the tank structure. A limitation of the current MPG technique is that it does not work in environments with changing pressure; during my internship I also made fundamental contributions to the development of the Spectral Density Propellant Gauging Method, a technique that does not depend on the stiffness of the tank walls.